PENERAPAN METODE PEMBELAJARAN THINK TALK WRITE (TTW) TERHADAP KETERAMPILAN MENULIS PUISI PADA SISWA SEKOLAH DASAR - Rahman, Ismi Aulia; Sugiharti, Rini Endah; Jasri, Hilda (PD PGMI se Indonesia, 2023)
This research aims to provide an overview of the application of the Think Talk Write (TTW) learning method to poetry writing skills in elementary school students. The method used in this research is Systematic Literature Review (SLR). This research was carried out by collecting data using various journals related to the required research variables. The data source used in this research is a journal or scientific article related to the application of the Think Talk Write (TTW) learning method to poetry writing skills in elementary school students using the classroom action research (PTK) method. It shows that the results of research in cycle I average value The students' average was 74.71 and in cycle II the students' average value increased to 81.71, so that the results of research using experimental research methods (quasi-experimental) based on the results of hypothesis testing can be seen tcount > ttable or 2.7936 > 1, 68, so Ho is rejected. The indicators for poetry writing skills are title/theme, word choice (diction), rhyme, imagination, message, imagery, language style and typography. Thus, the application of the Think Talk Write (TTW) learning method has a significant influence on elementary school students' poetry writing skills. The implications of this research are very effectively applied using the Think Talk Write (TTW) learning method for poetry writing skills.